Higher Education Quality Auditor Training in Vietnam (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article studies the issues related to training, qualifying and certification of highereducation quality auditors in Vietnam. Following the generic two-tier model of training anddevelopment of auditors, however Vietnam's methods of implementation are very different fromthe rest of the world and the ways of conducting are also very different in different regions of thecountry. The article analyzes and compares policies, experience, content and implementation ofthe auditor training programs in Vietnam compared with those of other countries in the world,thereby drawing suggestions for improvement solutions for autonomous auditing and accreditingagencies based auditors training centers and recommending policy changes to Vietnam'sMinistry of Education and Training and related agencies such as the National Council for HigherEducation Accreditation.